Effect of different photo-initiators and light curing units on degree of conversion of composites - William Cunha Brandt; Luis Felipe Jochims Schneider; Elisabete Frollini; Lourenço Correr-Sobrinho; Mário Alexandre Coelho Sinhoreti (Brazilian Oral Research, 2010)
The aim of this study was to evaluate: (i) the absorption of photo-initiators and emission spectra of light curing units (LCUs); and (ii) the degree of conversion (DC) of experimental composites formulated with different photo-initiators when activated by different LCUs. Blends of BisGMA, UDMA, BisEMA and TEGDMA with camphorquinone (CQ) and/ or 1-phenyl-1,2-propanedione (PPD) were prepared. Dimethylaminoethyl methacrylate (DMAEMA) was used as co-initiator. Each mixture was loaded with 65 wt% of silanated filler particles. One quartz-tungsten-halogen - QTH (XL 2500, 3M/ESPE) and two lightemitting diode (LED) LCUs (UltraBlue IS, DMC and UltraLume LED 5, Ultradent) were used for activation procedures. Irradiance (mW/cm²) was calculated by the ratio of the output power by the area of the tip, and spectral distribution with a spectrometer (USB 2000). The absorption curve of each photo-initiator was determined using a spectrophotometer (Varian Cary 5G). DC was assessed by Fourier transformed infrared spectroscopy. Data were submitted to two-way ANOVA and Tukey's test (5%). No significant difference was found for DC values when using LED LCUs regardless of the photo-initiator type. However, PPD showed significantly lower DC values than composites with CQ when irradiated with QTH. PPD produced DC values similar to those of CQ, but it was dependent on the LCU type.